CAFF Map No.51 - The distribution of known breeding colonies of Ivory Gull Pagophila eburnean within the Arctic - Arctic Council , Conservation of Arctic Flora and Fauna Working Group (CAFF International Secretariat, 2008)
CAFF Map No.51 - The distribution of known breeding colonies of Ivory Gull Pagophila eburnean within the Arctic, 2008